2004
DOI: 10.1111/j.1471-4159.2004.02379.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the extracellular domains of glutamate‐gated chloride channel α3 and β subunits from ivermectin‐resistant Cooperia oncophora affect agonist sensitivity

Abstract: Two full-length glutamate-gated chloride channel (GluCl) cDNAs, encoding GluCla3 and GluClb subunits, were cloned from ivermectin-susceptible (IVS) and -resistant (IVR) Cooperia oncophora adult worms. The IVS and IVR GluCla3 subunits differ at three amino acid positions, while the IVS and IVR GluClb subunits differ at two amino acid positions. The aim of this study was to determine whether mutations in the IVR subunits affect agonist sensitivity. The subunits were expressed singly and in combination in Xenopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
100
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 49 publications
7
100
0
5
Order By: Relevance
“…Unfortunately, this deletion is within a part of the subunit, the N-terminal 40 amino acids, that had to be removed to produce the recombinant protein used for the structural studies (87), so how this deletion might reduce the effects of ivermectin on the channel is obscure. Mutations in the extracellular ␤10 strand, including the L256F mutation found in a drug-resistant isolate of the parasite Cooperia oncophora (85), and the M2-M3 linker region of AVR-14B affect the binding of ivermectin to the channel (83,93), consistent with the contacts observed between bound ivermectin and the M2-M3 linker in GLC-1 (87).…”
Section: Structuresupporting
confidence: 55%
“…Unfortunately, this deletion is within a part of the subunit, the N-terminal 40 amino acids, that had to be removed to produce the recombinant protein used for the structural studies (87), so how this deletion might reduce the effects of ivermectin on the channel is obscure. Mutations in the extracellular ␤10 strand, including the L256F mutation found in a drug-resistant isolate of the parasite Cooperia oncophora (85), and the M2-M3 linker region of AVR-14B affect the binding of ivermectin to the channel (83,93), consistent with the contacts observed between bound ivermectin and the M2-M3 linker in GLC-1 (87).…”
Section: Structuresupporting
confidence: 55%
“…In both species, gene expression was detected in extrapharyngeal neurons in the head, sensory neurons, and ventral cord motor neurons and in H. contortus expression of the GluCl␣3A subunit was also detected in amphid neurons with the GluCl␣3B subunit found in three putative pharyngeal neurons. Mutations in avr-14 have been associated with avermectin resistance in C. elegans and C. oncophora (Dent et al, 2000;Njue et al, 2004). In C. oncophora, three amino acid differences, E114G, V235A, and L256F, were found between the GluCl␣3 subunits from avermectin-susceptible and -resistant worms.…”
mentioning
confidence: 99%
“…The gene is alternatively spliced in most of these species to yield two subunits, GluCl␣3A and GluCl␣3B, that share a common N-terminal ligand-binding domain but differ in the C-terminal channel-forming domains. Previous studies on these subunits have indicated that the GluCl␣3B subunit can form channels that bind radiolabeled ivermectin (22,23-dihydroavermectin B1 a ) (Campbell et al, 1983) with very high affinity (Cheeseman et al, 2001) and are activated by L-glutamate-and ivermectin when expressed alone, but that the GluCl␣3A subunit cannot (Dent et al, 2000;Njue et al, 2004;Yates and Wolstenholme, 2004;Tandon et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, ivermectin resistance is emerging as a serious problem in nematodes and arthropods (4 -6). In several instances, resistance has been shown to be caused by mutations that reduce the GluClR ivermectin sensitivity (7)(8)(9). Insight into the binding mechanisms of ivermectin at the GluClR may contribute to the understanding of ivermectin resistance mechanisms and to the development of a much needed new generation of anthelmintic drugs.…”
mentioning
confidence: 99%